Correlation of cag-A serological status with histological parameters of chronic gastritis among dyspeptic patients in south western Nigeria (2012)
"BACKGROUND:The aim of this study was to determine the sero-prevalence of Cag-A strains of Helicobacter pylori in both dyspeptic and non-dyspeptic individuals and also correlate the serological status of Gag-A strain of H. pylori with the various graded histological variables of chronic gastritis in the dyspeptic patients. METHODS:Using helicobacter p120 Cag-A enzyme linked immunosorbent assay, Cag-A serology test was carried out on 65 dyspeptic patients and 65 age and sex matched non-dyspeptic controls. The gastric biopsies of the patients were also histologically examined to ascertain the presence, nature and degree of the following histological variables of gastritis: colonisation by H. pylori; inflammation, intestinal metaplasia and mucosal atrophy. The CagA serological status was then correlated with the graded variables. RESULTS:A prevalence of 46.2% and 58.8% seropositivity for Cag-A strain of H. pylori was found among dyspeptic patients and control individuals respectively. Cag-A seropositive patients accounted for nine(81.8%) of the 11 cases with moderate to severe activity and 75% of both cases with mucosal atrophy and cases with intestinal metaplasia. CONCLUSION:Infection with Cag-A positive Helicobacter pylori was equally prevalent among both dyspeptic patients and control subjects studied. CagA seropositivity, however, appeared to be associated with higher inflammatory activity in the mucosa of patients with chronic gastritis and may be associated with intestinal metaplasia and mucosal atrophy in H. pylori-induced chronic gastritis."